The prognostic role of the echocardiographic tricuspid annular plane systolic excursion/systolic pulmonary arterial pressure (TAPSE/sPAP) ratio and its relationship with NT-proANP plasma level in systemic sclerosis - Grimaldi, Maria Chiara; Rosato, Edoardo; D’Angelo, Adriano; Cristiano, Ernesto; Marchitti, Simona; Volpe, Massimo; Rubattu, Speranza; Romaniello, Antonella (Frontiers in Cardiovascular Medicine, 2023)
Background: The tricuspid annular plane systolic excursion/systolic pulmonary arterial pressure (TAPSE/sPAP) ratio is an echocardiographic estimation of the right ventricle to pulmonary artery (RV/PA) coupling, with a validated prognostic role in different clinical settings. Systemic sclerosis (SSc) patients without evident cardiovascular involvement frequently display subtle RV impairment. The amino-terminal atrial natriuretic peptide (NT-proANP) plasma level relates to SSc disease progression and mortality. We aimed to assess the prognostic value of the TAPSE/sPAP ratio and its relationship with NT-proANP plasma level in SSc patients without overt cardiovascular involvement. Methods: We retrospectively analysed 70 SSc consecutive patients, with no clinical evidence of cardiovascular involvement or pulmonary hypertension, and 30 healthy controls (HC) in a retrospective, single-centre study. All SSc patients underwent recurrent clinical and echocardiographic assessments and NT-proANP plasma level was assessed at baseline. SSc-related cardiovascular events and deaths were extracted during a 6-year follow-up. The complete work-up for the diagnosis, treatment and management of pulmonary hypertension performed along the 6 years of follow-up referred to the 2015 European Society of Cardiology guidelines. Results: SSc patients showed lower TAPSE/sPAP ratio (mm/mmHg) at baseline compared to HC [HC median value=1.00 (0.96-1.05) versus SSc median value=0.71 (0.62-0.88); p<0.001]. Multivariable Cox analysis revealed TAPSE/sPAP ratio as an independent predictor for SSc-related cardiovascular events [HR=3.436, 95% CI 1.577-7.448; p=0.002] and mortality [HR=3.653, 95% CI 1.712-8.892; p=0.014]. The value of TAPSE/sPAP ratio < 0.7 mm/mmHg was identified as optimal cut-off for predicting adverse outcomes (p<0.001) by ROC analyses. NT-proANP level significantly related to TAPSE/sPAP ratio (r=0.52, p<0.001). TAPSE/sPAP ratio combined with NT-proANP showed an overall significant prognostic role in this SSc population, confirmed by Kaplan Meier analysis (Log rank p<0.001). Conclusion: The TAPSE/sPAP ratio, as an index of RV/PA coupling, is an affordable predictor of cardiovascular events and mortality in SSc and, combined with NT-proANP level, may improve the clinical phenotyping and prognostic stratification of SSc patients.